(untitled) (Observatorio Económico, 2009)
In a year in which the Chilean economy looks set to grow little or not at all, an injection of self-esteem does no harm. We are not talking about relapsing into the adolescent egocentrism of the early 1990s, with executives holding forth in VIP lounges about the jaguars of Latin America. Continue reading...